2015
DOI: 10.1109/tps.2015.2428696
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Controllable Atmospheric Plasma Source

Abstract: An atmospheric pressure plasma source in which the gas temperature can be accurately controlled from below freezing point up to a high temperature has been developed. In general plasma devices, an electrical discharge is passed through a gas at about room temperature to generate plasma, so the plasma is at a temperature higher than room temperature; moreover, the gas temperature is determined by the discharge condition such as discharge power and plasma gas flow rate, so accurate temperature control is difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…The plasma gas temperature was measured using a thermocouple to simplify the measurement Oshita et al 2015 . In our experiments, 3% oxygen gas was added to the temperature-controlled helium gas before being introduced into the plasma generating unit.…”
Section: Temperature-controllable Plasma Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…The plasma gas temperature was measured using a thermocouple to simplify the measurement Oshita et al 2015 . In our experiments, 3% oxygen gas was added to the temperature-controlled helium gas before being introduced into the plasma generating unit.…”
Section: Temperature-controllable Plasma Sourcementioning
confidence: 99%
“…To overcome these problems, we proposed a temperature-controllable plasma technique PAT Japan: 4611409, U.S.: 8,866,389 and developed a plasma source Oshita et al, 2015 . This device can control the plasma gas temperature to between -50 and 160 with a standard deviation of 1 independently from the discharge power and plasma gas flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…This fact explains the exceedingly detailed procedures described under Materials and Methods for generating spore stocks and why it is necessary to adhere to them. Although the plasma gas temperature can be actively controlled [32], most plasma treatments reported in the literature are conducted at room temperature without tight control over the temperature at which the cells are being treated. The resistance of 13 vegetative cells to external stressors, however, can be quite sensitive to small temperature variations, and only a few degrees difference can drastically change the cell response.…”
Section: Reference Biological Agentmentioning
confidence: 99%
“…Moreover, it was confirmed that this plasma source generates stable plasmas with argon, helium, and nitrogen gases. The plasma source can be attached to a temperature controlled unit, 30 which allows a user to easily control plasma gas temperatures. Therefore, this correlates to the notion that such plasma gases can be accurately controlled at around body temperature and that heat-sensitive targets can be effectively treated without thermal damage.…”
Section: -11mentioning
confidence: 99%